Introducing hospitality. - 4 0 16; 5 (Australia : Video Education Australasia)
This program provides an insight into: how the hospitality industry has changed, its contribution to the economy, and what the current issues are for those working in the industry.
DVD format.
Keywords: 2 -- 0; 6; Hospitality industry. -- 20; 20; 2